ISLAM NUSANTARA: ANALISIS KONSEP PEMIKIRAN WASATHIYAH DAN FONDASI MODERASI ISLAM DI INDONESIA - Nurul Mustofa; Purna Wirawan; Sumiati; Hidayatuz Zainiyah (Jurnal Studi Pesantren, 2026)
Religious moderation in the perspective of Islamic archipelago is a concrete manifestation of the concept of wasathiyah (middle way) in Islam. This concept represents moderate Islamic thought that prioritizes the values of tawassuth, tawazun, I'tidal, and tasammuh as a tolerant and harmonious religious style and becomes  the  foundation  in  building  moderation  practices  in  Indonesia.  This research aims to analyze the concept of wasathiyah (moderate) thought in Islam Nusantara and how these ideas contribute to the formation of Islamic moderation in Indonesia. This research uses a qualitative approach with a literature study method. The results of the study show that Islam Nusantara as the concept of wasathiyah thinking has a major role in fostering religious moderation in Indonesia. Islam Nusantara is able to answer the challenges of the times such as Radicalism and Intolerance. This research is expected to make an academic contribution to strengthen  moderate  Islamic  discourse  and  become  a  reference  in  efforts  to maintain  religious  harmony  and  strengthen  social  integration  in  the  midst  of diversity.